Using LabVIEW software for remote voltage, current, and THD measuring and improving in the electrical grid - Gentian Dume; Alfred Pjetri; Andi Hida (Bulletin of Electrical Engineering and Informatics, 2026)
The increasing penetration of photovoltaic (PV) systems has raised concerns about power quality due to the harmonic distortion injected during DC–AC conversion by inverters. These harmonics can interfere with nearby electrical devices and compromise grid stability. This paper presents a LabVIEW-based virtual instrument designed specifically for real-time monitoring, analysis, and mitigation of voltage and current harmonics in grid-connected PV systems. The core contribution of this work lies in the development of an interactive, software-based platform that not only measures total harmonic distortion (THD) in real time but also allows users to design and simulate harmonic filters dynamically. The system achieved a reduction of current THD by 52% and voltage THD by 73% under tested conditions, demonstrating its effectiveness in improving power quality. Unlike conventional hardware-dependent solutions, the proposed tool offers a low-cost, easily customizable, and scalable approach suitable for educational laboratories, field diagnostics, and smart grid applications. By enabling remote control and filter tuning through LabVIEW, this solution supports the growing demand for intelligent power quality management and facilitates the seamless integration of renewable energy into modern electrical grids.